The novel Aspergillus fumigatus MAT1-2-4 mating-type gene is required for mating and cleistothecia formation - Yu, Yidong; Amich, Jorge; Will, Christine; Eagle, Carly E.; Dyer, Paul S.; Krappmann, Sven (Fungal Genetics and Biology, 2017)
Sexual propagation accompanied by recombination and the formation of spore-containing fruiting bodies is a cornerstone of fungal genetics and biology. In the human pathogen Aspergillus fumigatus sexual identity has previously been shown to be determined by MAT1-1-1 or MAT1-2-1 genes which act as transcriptional regulators and are present within idiomorphs found at the MAT locus. We here report the identification and first characterization of a further novel gene, termed MAT1-2-4, that is present in the MAT1-2 idiomorph of A. fumigatus. A mating-type swapping strategy was used to achieve an unbiased deletion of the MAT1-2-4 gene with no impact on MAT1-2-1 gene expression. Phenotypical characterization of the resulting strain revealed an inability to mate with the compatible MAT1-1 progenitor, demonstrating that the MAT1-2-4 gene product is a genuine mating-type factor required for correct sexual development. A GPI-anchored protein of unknown function was identified as interaction partner. However, no functional role in the mating process or ascosporogenesis could be demonstrated by deletion analysis for this latter protein, although a role in heterokaryon formation is suggested. Bioinformatic analysis also demonstrated the presence of MAT1-2-4 homologues in some, but not all, other Aspergillus species and the evolutionary origins and implications of the MAT1-2-4 gene are discussed.
EVALuna2:7737